Paku Baja : Upaya Meningkatan Karakter Siswa Melalui Sosialisasi Unggah - Ungguh Basa Jawa - Hardono Hardono; Kezia Kurnia; Syarofina Hernila; Catur Wulandari; Shidiq Hema; Endah Tri; Savina Dina; Anastasya Gladly; Gabriella Caroline (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Politeness, for Javanese people is very important. Javanese culture highly upholds politeness or Eastern customs. A person's manners can be seen and assessed from their behavior (patrap) and speech (subasita/unggah-ungguh). So there is a proverb that says